Influence of a Post-dam Sediment Pulse and Post-fire Debris Flows on Steelhead Spawning Gravel in the Carmel River, California - Smith, Douglas P.; Schnieders, Jamie; Marshall, Lauren; Melchor, Katherine; Wolfe, Skylar; Campbell, Devon; French, Alyssa; Randolph, Joseph; Whitaker, Mattole; Klein, Joseph; Steinmetz, Cory; Kwan, Ruby (Frontiers in Earth Science, 2021)
Spawning gravel scarcity is a limiting factor for successful recovery of federally-threatened anadromous fish like steelhead of central California. A BACI-experimental design using bed particle counts from 2013 through 2021 shows that spawning-sized gravel (32 mm to 90 mm) diminished downstream of the former San Clemente Dam site in 2017, following dam removal in 2015. High flows in 2017 transported a pulse of sand and fine-gravel that filled pools and runs throughout the river below the dam. The bed material in the 3 km closest to the dam remained too coarse for redds in riffles and too fine in pools and runs. Time-series bathymetric data of the Los Padres Dam reservoir located in the upper Carmel watershed shows that nearly all bed material (including spawning gravel) in the upper Carmel River watershed was recruited during wet winters that immediately followed expansive wildfires. We studied that effect in detail following the Carmel Fire of August 2020, which preconditioned the slopes adjacent to the Carmel River for debris flows. Our analysis of several fire-mediated debris flows in 2021 show that they contained virtually no mud and held approximately 45% spawning-sized gravel. Although the debris flows contained abundant spawning gravel, and several flow snouts terminated in the Carmel River, the material was dispersed downstream rather than forming bars and patches that could be used for steelhead nest building. The generally small volume of material in the flows relative to the size of the river channel and impediments to debris flow runout limited the contribution of spawning-size gravel to the river.